Assessing the Pedagogical Quality of Geospatial Content in Indonesian High School Geography Textbooks - Mohammad, Gustiano; Fernandes, Genito Xavier (Future Space: Studies in Geo-Education, 2025)
A textbook is a book that helps teach certain knowledge. Despite their noble purpose, in reality there are textbooks that are arguably less suited to function as such. Various researchers found errors in the content presented by textbooks and the way they are presented. To maintain the quality of textbooks, regulations regarding books are issued as discussed in Permendikbudristek Number 25 of 2022. Through this regulation, the government emphasizes the suitability of 4 aspects of books, namely materials, language, design and graphics (printing). This study aims to evaluate the suitability of the Grade 10 High School Geography textbook specifically on the topics of Maps, Remote Sensing, and Geographic Information Systems, aligned with the curriculum's Learning Outcomes. The way to evaluate suitability is to assess three aspects, namely material, language and design aspects with the help of a modified book resensing instrument from BNSP. The results of this textbook assessment can be seen from the suitability of 95.69% of the material, which means that the content of this textbook is correct and in accordance with BNSP standards. Meanwhile, the language aspect scored 93.75%, categorized as very good, indicating communicative language use despite minor grammatical imperfections. Lastly, the design aspect is 90.00%, the visuals presented are quite good and appropriate.